Association of crown-root ratio and tooth survival in Chinese patients with advanced periodontitis: An 11-year retrospective cohort study - Shi, Shu-wen; Meng, Yang; Jiao, Jian; Shi, Dong; Feng, Xiang-hui; Meng, Huan-xin (Journal of dentistry, 2024)
Periodontitis is a chronic multifactorial inflammatory disease which eventually lead to tooth loss (TL). Therefore, a retrospective study was conducted to evaluate the status of tooth survival within 11 years after non-surgical periodontal treatment (NSPT) and to analyze the risk factors especially crown-root ratio (CRR) that affected TL in Chinese with advanced periodontitis. 3481 teeth of 131 subjects who underwent NSPT were examined retrospectively within a mean follow-up period of 11.6 years. The association of risk factors including clinical and radiographic parameters with TL was assessed using univariate and multivariate Cox regression analyses. Smooth curve fitting and segmented regression model were conducted to show the nonlinear relationship and the threshold effect between CRR and the risk of TL. 347 teeth were lost in 97 patients in this study. Male, diabetes mellitus, heavy-smoker, molar, probing depth (PD), attachment loss (AL), bleeding on probing (BOP), tooth mobility, and radiographic bone loss were significantly associated with tooth loss (P < 0.05). A nonlinear relationship between CRR and the risk of TL was found, with different turning point values between molars and non-molars (1.9 vs. 2.76). The findings based on practice-based clinical and radiographic data do suggest a nonlinear relationship between CRR and the survival of teeth, and provide evidence to help clinicians to determine the prognosis of teeth for patients with advanced periodontitis. Based on clinical and radiographic data, this study provides an individualized basis for clinicians to judge the dental prognosis of patients with advanced periodontitis according to the different tooth sites.